The Ancient Biosphere - Nowlan, Godfrey (Geoscience Canada)

(untitled) (The Geological Association of Canada, 1993)
Abstract The origin and development of life on Earth is intimately linked to the physical evolution of the planet's surface and upper lithosphère. The future of research on the ancient biosphere is filled with as much excitement and uncertainty as the future of the Earth itself. The trend will be to build on traditional strengths, such as biochronology, paleoecology and paleobiogeography, and to seek completely new research directions driven by new technology, new concepts, and new requirements for information. The traditional strength of paleontology in providing the time scale necessary for evaluating the duration and rates of physical processes will remain important. Biostratigraphy will be more closely integrated with new concepts inphysical stratigraphy, such as event and sequence stratigraphy. Paleoecological and paleobiogeographical data, which only fossils can provide, will be morefully interpreted to produce refined models of basin processes. Studies of extinction and radiation of the Earth's biota through time will lead to a fuller understanding of biological evolution and its relationship to the physical evolution of the Earth. The desire to test the Gaia Hypothesis will spur much of this research. The application of new technologies will greatly enhance our ability to study fossil organisms without damaging specimens. Computer technology will permit better data management, and manipulation and display of both data and images, thus enhancing our interpretive skills. The integration of paleontology with geochemisty will result in a profound improvement in our understanding of paleo-oceanography and paleobiogeography. The chemistry of fossils, reflecting the chemistry of the oceans in which they lived, will allow interpretation of large-scale trends, and greater understanding of events such as extinctions and radiations. In terms of organic geochemistry, paleontology will be taken to the molecular level, moving beyond the economically driven study of bio-markers to elaboration of the temporal distribution of biomolecules and their implications for evolution. Understanding the evolution of the biosphere is of crucial importance to interpreting global change, an issue that will grow in public importance during the coming decade. In order to appreciate the impact and rate of global changes in the ancient and present biosphere, there is a requirement for a clearer understanding of biodiversity. Recent trends indicating a decline of systematic paleontology and biology will have to be reversed if we are to gain a comprehensive view of global change. Research on the ancient biosphere is of increasing importance to the future of the planet — particularly to its human population — as it becomes more evident that the continuing survival of the species is in doubt. A prime component of future scientific work must be the explanation and interpretation of results to the general public. Development of scientific literacy is perhaps the most pressing challenge facing the scientific community.